Makna Tuturan Sae Pah dalam Wilayah Desa Bo’en Kecamatan Rinhat Kabupaten Malaka - Markus Bani; Yustina Sako; Rozario M. Da Costa; Adrianus Berek (Lembaga Pengembangan Kinerja Dosen, 2024)
From the research title The Meaning of Sae Pah Speeches, with this the researcher's aim is to describe the meaning of the Sae Pah Speeches in the Bo'en Village area, Rinhat District, Malacca Regency. The problem that will be discussed in this research is the meaning contained in the sae pah speech in Bo'en Village, Rinhat District, Malaka Regency. The aim of this research is to describe the meaning in the traditional sae pah ritual speech in the Bo'en community, Rinhat District, Malacca Regency. The method used in this research is a qualitative descriptive method. (Bogda and Tyilor) Aminudin, 1990: 15, stated that the qualitative descriptive method is research that produces descriptive data in the form of written words or writings about people whose behavior is being observed. The researcher concluded that Sae Pah speech in Boen Village is very important so that people understand the meaning of Sae Pah speech and the characteristics which then form groups that have different traditions, languages ​​and beliefs and can function for the people of Boen Village. So that the Sae Pah traditional speech of the ancestors needs to be preserved by the younger generation, because the Sae Pah traditional speech culture has good value to be a positive impact of the attachment of norms in the traditions of the Boen Village community. As for the suggestions that the author gives to the Boen Village community in general and in particular so as to continue to maintain and preserve the diversity of Sae Pah traditional speech values. To maintain the values ​​of Sae Pah traditional speech contained therein so that they can continue into the next generation. The principle is that it is not influenced and shifted by other cultures (westernization).